Titulacion mancomunada en Nicaragua, Indonesia y Honduras : sintesis de diagnosticos rapidos - Lastarria-Cornhiel, Susana (Land Tenure Center, University of Wisconsin-Madison, 2003)
Numerous titling and registration programs have been implemented in Latin America, Africa, Asia, and Eastern Europe as a necessary measure to ensure the property rights of smallholders and increase their access to other production factors, particularly credit. A major criticism of titling programs and formal property rights institutions (such as property registries), however, is their tendency to grant title for household landed property to just one person in the household, usually the male head of household. As a response, the mechanism of joint titling (titling both wife and husband) has been often recommended and is being implemented in a number of countries. Rapid appraisals undertaken in these countries explored the implementation and effectiveness of joint titling programs. The results suggest that while some measures improve the effectiveness of joint titling, such as legislation that explicitly addresses the issue of gender equity and joint titling and including gender training in the implementation of titling and registration programs, cultural obstacles continue to deny women legal recognition of their land rights.
Joint titling in Nicaragua, Indonesia, and Honduras : rapid appraisal synthesis [Spanish]
76 p.
Keywords: Land titles Nicaragua; Land titles Indonesia; Land titles Honduras